Figurative Language in the Song Lyrics of Feby Putri’s Riuh Album as an Alternative Literature Teaching Material for Senior High School Students - Rodiasari, Dhea Aulia; -, Sumartini (Bahasa Indonesia Prima, 2026)
This study aims to describe the use of figurative language in the lyrics of the album Riuh by Feby Putri and to analyze its relevance as an alternative teaching material for literature at the high school level. The methods used in this study include a qualitative approach employing content analysis and descriptive analysis. Data were collected through a literature review by reading, marking, and recording figurative language data in ten songs from the album. The results revealed 28 instances of figurative language classified into three main categories: figures of comparison, including metaphors (7), personification (5), and similes (2); figures of contrast, including paradox (8), hyperbole (3), and apostrophe (1); and figures of repetition in the form of anaphora (2). Further analysis indicates that the song lyrics in the Riuh album meet the criteria for suitability as literary teaching materials based on their poetic yet communicative linguistic aspects, as well as their psychological and cultural aspects that reflect the emotional dynamics of high school-aged adolescents. Thus, this album can be implemented as an alternative literary teaching resource to help students understand various figures of speech in literary texts.